2018
DOI: 10.1111/opo.12457
|View full text |Cite
|
Sign up to set email alerts
|

Optical ‘dampening’ of the refractive error to axial length ratio: implications for outcome measures in myopia control studies

Abstract: There was a significant negative correlation between MSE and AXL for all age groups (all p < 0.005). RX: AXL ratios for participant data were compared with the ratio generated from Gullstrand model eyes. Both modelled and actual data showed non-linearity and non-constancy, and that as axial length is increased, the relationship between myopia and axial length differs, such that it becomes more negative. Conclusions: Optical theory predicts that there will be a reduction in the RX: AXL ratio with longer eyes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 26 publications
(27 reference statements)
1
32
1
Order By: Relevance
“…37 We discovered a 0.059 reduction in SE:AL ratio per 1-mm increase in AL for the 3-to 21-year olds, 0.055 for the 22to 40-year olds, 0.046 for the 41-to 59-year olds, and 0.037 for the group no younger than 60 years. However, Cruickshank et al 36 observed a 0.05 reduction per 1-mm increase in AL for all age groups. We then carefully analyzed the plotted figures showing a reduction of 0.05/mm and the equations reflecting the relationship between refractive error and AL for varying ages and found an obviously decreasing slope of the reduction as age increased.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…37 We discovered a 0.059 reduction in SE:AL ratio per 1-mm increase in AL for the 3-to 21-year olds, 0.055 for the 22to 40-year olds, 0.046 for the 41-to 59-year olds, and 0.037 for the group no younger than 60 years. However, Cruickshank et al 36 observed a 0.05 reduction per 1-mm increase in AL for all age groups. We then carefully analyzed the plotted figures showing a reduction of 0.05/mm and the equations reflecting the relationship between refractive error and AL for varying ages and found an obviously decreasing slope of the reduction as age increased.…”
Section: Discussionmentioning
confidence: 88%
“…We then carefully analyzed the plotted figures showing a reduction of 0.05/mm and the equations reflecting the relationship between refractive error and AL for varying ages and found an obviously decreasing slope of the reduction as age increased. Thus, we assumed that Cruickshank et al 36 obtained an approximate value of 0.05/mm reduction for all age groups due to the narrow age range in their study. Consequently, the wide age ranges in our study would help better understand the relationship between refractive error and AL.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Axial length rather than myopic refractive error should be the primary target for myopia management. It therefore needs to be assessed at each visit . Axial length does not have a stable growth rate with age, nor is it similar among the sexes and ethnicities, therefore, axial length should be related to its published growth curve per gender and ethnicity .…”
Section: Myopia Managementmentioning
confidence: 99%
“…The axial elongation responsible for causing myopia in most patients puts the eye at a greater risk of ocular pathology . Cruickshank and Logan explain why axial length and refractive error should not be used interchangeably, and provide both theoretical and empirical evidence that the relationship between axial length and refractive error differs in longer eyes as opposed to shorter eyes …”
mentioning
confidence: 99%